Exercise 7.2
Page-7.6Question 1:
Write two solutions for each of the following equations:
(i) 3x + 4y = 7
(ii) x = 6y
(iii) x + xy = 4
(iv)
Answer 1:
(i) We are given,
Substituting x = 1 in the given equation, we get
Substituting x = 2 in the given equation, we get
(ii) We are given,
Substituting in the given equation, we get
Substituting in the given equation, we get
(iii) We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 4 in the given equation, we get
(iv) We are given,
Substituting x = 0 in the given equation, we get
Substituting x = 3 in the given equation, we get
Question 2:
Check which of the following are solutions of the equations 2x − y = 6 and which are not:
(i) (3,0)
(ii) (0,6)
(iii) (2, −2)
(iv)
(v)
Answer 2:
We are given,
2x – y = 6
(i) In the equation 2x – y = 6,we have
Substituting x = 3 and y = 0 in 2x – y, we get
is the solution of 2x – y = 6.
(ii) In the equation 2x – y = 6, we have
Substituting x = 0 and y = 6 in 2x – y,we get
is not the solution of 2x – y = 6.
(iii) In the equation 2x – y = 6,we have
Substituting x = 2 and y = –2 in 2x – y, we get
is the solution of 2x – y = 6.
(iv) In the equation 2x – y = 6, we have
Substituting and y = 0 in 2x – y, we get
is not the solution of 2x – y = 6.
(v) In the equation 2x – y = 6, we have
Substituting and y = –5 in 2x – y, we get
is the solution of 2x – y = 6.
Question 3:
If x = −1, y = 2 is a solution of the equation 3x + 4y = k, find the value of k.
Answer 3:
We are given,
is the solution of equation
.
Substituting and
in
,we get
Question 4:
Find the value of λ, if x = −λ and y = is a solution of the equation x + 4y − 7 = 0.
Answer 4:
We are given,
is the solution of equation
.
Substituting and
in
,we get
Question 5:
If x = 2α + 1 and y = α − 1 is a solution of the equation 2x − 3y + 5 = 0, find the value of α.
Answer 5:
We are given,
is the solution of equation
.
Substituting and
in
,we get
Question 6:
If x = 1 and y = 6 is a solution of the equation 8x − ay + a2 = 0, find the value of a.
Answer 6:
We are given,
is the solution of equation
.
Substituting and
in
,we get
Using quadratic factorization
Question 7:
Write two solutions of the form x = 0, y = a and x = b, y = 0 for each of the following equations:
(i) 5x − 2y = 10
(ii) −4x + 3y = 12
(iii) 2x + 3y =24
Answer 7:
(i) We are given,
Substituting x = 0 in the given equation, we get
Substituting y = 0 in the given equation, we get
(ii) We are given,
Substituting in the given equation, we get
Thus x = 0 and y = 4 is the solution of the −4x + 3y = 12
Substituting y = 0 in the given equation, we get
(iii) We are given,
Substituting x = 0 in the given equation, we get
Substituting y = 0 in the given equation, we get
No comments:
Post a Comment